Vertical marginal discrepancies of metal castings obtained using different pattern materials: A scanning electron microscope study - R Sushma; Anand Farias; Romesh Soni (Wolters Kluwer Medknow Publications, 2014)
Background and Objectives: Dental Casting involves various stages of processing, out of which any may affect the dimensional accuracy. The fit of a casting depends not only on the method of fabrication employed but also on the type of materials utilized. One important variable in the casting process is the type of pattern material employed. This study was carried out to determine and compare the effect of different pattern materials on the vertical marginal accuracy of complete cast crowns. Materials and Methods: A standardized metal master die simulating a prepared crown was used to prepare 60 models on which patterns were fabricated using Inlay Pattern Wax; Auto-polymerized Pattern Resin and Light Cured Modeling Resin and cast immediately. Castings of the patterns were subjected to analysis of marginal fit using a scanning electron microscope (SEM). Results: One-way ANOVA result showed a significant difference in the gap observed between the castings fabricated using the three types of pattern materials (P < 0.001). Post-hoc Bonferroni tests showed significant difference between the castings fabricated using Inlay Type B pattern wax and Auto-polymerized pattern resin as well as between Inlay Type B pattern wax and Light-cured modeling resin (P < 0.01). Significant difference exists between Auto-polymerized pattern resin and Light-cured modeling resin (P > 0.05). Conclusion: With strict adherence to the principles of pattern fabrication and immediate casting, Inlay wax can still be the pattern material of choice to produce a casting with minimal marginal discrepancy with added advantages of being user friendly and cost effective.